Major Conflicts Between India and Pakistan: A Critical Analysis of Historical Tensions and Geopolitical Dynamics (Al-Qamar, 2024)
Relations between India and Pakistan have remained parallel end and worst hostile as well ever since independence in 1947. In nearly 75 years, there were three wars between the two and a number of serious localized military clashes, including those on Ran of Ketch in 1965, followed by Kargil in 1999.The disputed territory of Kashmir played a significant role to maintain continuity, focusing the past conflicts of 1947 and 1965. As these two countries exploded nuclear weapons in 1998, their long-standing hostility has attracted and seriously concerned by the international community that their competition could rise to a nuclear war and cause disasters to both countries and the world as well. Whereas the Kashmir including some other outstanding issues, such as, water dispute, Sir Creek, Siachen and boundary disputes have also recorded the extreme level of conflicts between the two rivalries. Regionalism has played a significant role in European continent; however, in South Asia hegemonic attitude of India has marginalized the role of regional organizations such as SAARC. The world and south Asia witnessed the changes over two decades after the cold war, the liberalization of world trade, the growth of fundamentalism and revolutionary changes in the field of communications. Recognizing the intensity of the relations, India and Pakistan’s changing regional and international affairs which has drastically impaled to the leaders and governments of both the countries to initiate talks on their outstanding issues. The cross-border talks were an initiative step which attempted to provide a new forum to debate on these substantive issues resulted in the division of the two nations. Keeping in view the cited developments and their influences on the relations between India and Pakistan, some factors remained constant, the unresolved dispute over Kashmir, the growth of military spending, moves towards Nuclearization and perpetuation of an “adversarial psychosis” are still under question.This research has critically analyzed historic rivalry between India and Pakistan. It has also provided viable recommendations that how to contain major irritants between two States especially Kashmir issue and Nuclearization in region. In this research the purposive sampling method is used to justify the given hypothesis and objectives. The date is collected through the secondary data and results are deducted from the analytical approach.
Keywords: Indo-Pak Conflicts; Historical Tensions; Geostrategic and Geopolitical Dynamics